Effect of Food Security on Stunting Prevention via Protein Consumption Mediation - Pratama, Chris Candra Januar; Nazamuddin, B. S.; Dawood, Taufiq Carnegie (Graha Primera Saintifika, 2025)
The value of potential GDP lost due to stunting varies between countries. Stunting is not only an indicator of well-being but also a prerequisite for increasing productivity. The problem of stunting can lead to a decrease in productivity, which, in turn, can lead to lower economic output. Indonesia is one of the countries that still faces stunting problems. This study aims to analyze the role of protein consumption in mediating the effect of food security on stunting prevention in Indonesia. The data used is panel data covering 34 provinces in Indonesia for the period 2018-2021, resulting in 136 observations. The model used in this study is path analysis. There are two models estimated using panel data regression analysis: the stunting prevention equation model and the protein consumption equation model. Stunting prevention is estimated against the variables of food security and protein consumption. In the second model, the effect of food availability for consumption is estimated on consumption through the food security approach. The results show that increasing food security and protein consumption influences stunting prevention. Increasing food security affects protein consumption. Protein consumption mediates the effect of food security on stunting prevention. Government policies to increase protein consumption can be achieved through formal and informal education. Fiscal policies such as a sugar tax and a tax on unhealthy foods or drinks with low nutritional value can be applied to create a substitution effect that impacts increased protein consumption. Labor-intensive economic policy in the agricultural sector is also needed to promote food security, protein consumption, and stunting prevention simultaneously.